Hubungan antara Penguasaan Tata Bahasa dengan Keterampilan Menulis Narasi Bahasa Inggris Siswa Kelas XI SMK Negeri 2 Depok - Prita Pantau Putri Santosa (Deiksis, 2017)
The goal of this research is to analyse and prove the correlation between grammar mastery and students’English narrative writing skill at the 11th grade of SMK Negeri 2 Depok. Research data was collected by giving multiple cohoice tests of grammar and narrative writing skill. Furthermore, the data was analyzed quantitatively in order to know correlation coefficient, determination coefficient and signifinancy coefficient as part of hypothesis test. Data analysis was conducted with ? = 0,05. Based on the result of hypothesis test, the researcher has found the significant correlation of grammar mastery and  students’ English narrative writing skill.  Kata Kunci: Penguasaan Tata Bahasa, Ketrampilan Menulis Narasi